PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA SMP N 1 RAMBAH HILIR ANTARA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) DAN NUMBERED HEAD TOGETHER (NHT) - Yulianti, Iin; -, Arcat; -, Suwandi (Universitas Pasir Pengaraian, 2015)
This research aims to determine the differences in students mathematic learning outcomes SMP N 1 Rambah Hilir between the use of cooperative learning model Student Teams Achievement Divisions (STAD) and Numbered Head Together (NHT). In this study the formulation of the problem is